Pleurothallis mark-wilsonii a new species from the subsection Acroniae series Amphigyae from the Western Andes of Colombia - Moreno, Juan Sebastián; Sierra-Ariza, Mario Alexei; Hoyos, David; Galindo-Tarazona, Robinson (Phytotaxa, 2022)
A new species of Pleurothallis from the Western Andes of Colombia is described and illustrated. The new species belongs to subsection Acroniae of the series Amphigyae, morphologically resembles Pleurothallis amphigya, but differs mainly by the ovate-lanceolate lip, with two divergent, elongate keels, located at the base up to about the middle of the lip (vs. triangular trilobed, the disc with a developed glenion at the base).